2005
DOI: 10.17305/bjbms.2005.3288
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Gentamicin-induced Acute Tubular Necrosis in Rats

Abstract: Gentamicin is still widely used in clinical practice in spite of its renal toxicity. The role of nitric oxide (NO) in that process is not completely elucidated. The aim of this study was to investigate the relationship between plasma level of NO and the histopathological changes of kidney in acute tubular necrosis (ATN) induced by gentamicin in rats. Study was carried out in Albino-Wistar rats, both sexes (n=16), average body weight 200-250 g. divided in two equal groups: control and gentamicin group. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Maldanado et al (2003) have shown increase in nitrosation of tyrosine residues in the proteins of kidney in gentamicin-treated rats. In a recent study, Nakas-Icindic et al (2005) have shown rise in plasma levels of nitric oxide in gentamicin-treated rats. These studies and the present study provide evidence for the role of nitrosative stress in gentamicin-induced renal damage in the rat.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Maldanado et al (2003) have shown increase in nitrosation of tyrosine residues in the proteins of kidney in gentamicin-treated rats. In a recent study, Nakas-Icindic et al (2005) have shown rise in plasma levels of nitric oxide in gentamicin-treated rats. These studies and the present study provide evidence for the role of nitrosative stress in gentamicin-induced renal damage in the rat.…”
Section: Discussionmentioning
confidence: 91%
“…Increased Author for correspondence: Premila Abraham, Department of Biochemistry, Christian Medical College, Bagayam, Vellore 63202, Tamil Nadu, India (fax π91 416 2262268, e-mail premilaabraham/ yahoo.com). nitro tyrosine levels in the kidney and increased nitrite and nitrate levels in the kidney and plasma of gentamicin-treated rats (Rivas-Cabanero et al 1994;Nakas-Icindic et al 2005) have been reported.…”
mentioning
confidence: 97%
“…In this study, renal tissue MDA and NO levels were statistically high in AK treated group. Another study has shown that plasma NO levels and the nephrotoxivity was statistically high in gentamicin treated rats 39 .…”
Section: Discussionmentioning
confidence: 96%
“…This effect was evident by the decline in renal MDA level, plasma urea, and plasma creatinine Two roles have been played by NO, physiological and pathophysiological roles (Carlstrom et al, 2009) and have a significant role in the function of renal tubular and renal hemodynamics regulation (Patel et al, 1999). Group treated with gentamicin revealed significant increment in the level of NO; acute renal failure occurred due to gentamicin is as a result of the free radical nature of NO (Nakas-Ićindić et al, 2005) Also, NO produced cytotoxic peroxynitrite, as a result of interaction with superoxide radical which resulting in tubular cells injury and renal failure (Christo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%